Learn from Home with a Simple Think Pair Share - Luh Ketut Sri Widhiasih (Yavana Bhasha : Journal of English Language Education, 2021)
online. Meanwhile, mastering writing skill is still important in online class because thesubjects will be able to express their ideas, feeling and experiences in the written formappropriately. The objective of this study was to find out whether or not writing skill ofsecond semester students of English Language Education Study Program, Faculty ofTeacher Training, Mahasaraswati Denpasar University in Academic year 2019/2020 couldbe improved trough Think Pair Share with distance learning model. The study wasdesigned in the form of classroom action research. Based on the result of the pre-test,post-test, and questionnaire, it could be concluded that writing skill of the secondsemester students of English Language Education Study Program, Faculty of TeacherTraining, Mahasaraswati Denpasar University in Academic Year 2019/2020 could beimproved trough Think Pair Share with distance learning model.